2021
DOI: 10.1002/pts.2570
|View full text |Cite
|
Sign up to set email alerts
|

Active cellulose acetate‐carvacrol films: Antibacterial, physical and thermal properties

Abstract: Cellulose acetate (CA) is a low cost, biodegradable polymer obtained from renewable resources. The development of CA active films to reduce or inhibit microbial growth in food could increase food products' shelf‐life while decreasing the use of petroleum‐based non‐biodegradable polymers on food packaging. In this work, CA films containing carvacrol, a major antimicrobial compound in oregano essential oil, were obtained by solvent‐casting and extensively characterised. Results showed that carvacrol in concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Among the volatile antimicrobial substances, essential oils have been extensively studied due to their strong antimicrobial efficacy, natural origin and comparatively harmless effect on human health 9–11 . Various essential oils have been integrated into packaging films or edible coatings as an antimicrobial substance 8,12–15 . Cinnamon essential oil (CEO) is one of the most studied EO, which according to Ojagh et al 12 has shown a broad spectrum of antimicrobial activity, including combatting food spoilage bacteria such as L. monocytogenes , Pseudomonas fluorescens and Escherichia coli 12,16–23 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the volatile antimicrobial substances, essential oils have been extensively studied due to their strong antimicrobial efficacy, natural origin and comparatively harmless effect on human health 9–11 . Various essential oils have been integrated into packaging films or edible coatings as an antimicrobial substance 8,12–15 . Cinnamon essential oil (CEO) is one of the most studied EO, which according to Ojagh et al 12 has shown a broad spectrum of antimicrobial activity, including combatting food spoilage bacteria such as L. monocytogenes , Pseudomonas fluorescens and Escherichia coli 12,16–23 .…”
Section: Introductionmentioning
confidence: 99%
“…6 If antimicrobial packaging is to show an antimicrobial activity through the headspace, volatile antimicrobial agents should be incorporated into the packaging. 7,8 Among the volatile antimicrobial substances, essential oils have been extensively studied due to their strong antimicrobial efficacy, natural origin and comparatively harmless effect on human health. [9][10][11] Various essential oils have been integrated into packaging films or edible coatings as an antimicrobial substance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MAM is a precursor of N-halamines, which were used for the modification of cellulose due to their high efficacy against various microorganisms and rechargeability . CA and poly­(vinyl chloride) (PVC) were selected as models to make plastic films because the former is one of the most widely used cellulose derivative plastics with excellent optical and mechanical properties, and the latter is a common plastic in the polyethylene “family” that has low cost, easy processability, and broad applications . The effect of modified CNCs on the mechanical and optical properties of CA and PVC films was investigated, and the antibacterial property and rechargeability of composite materials were evaluated with two common foodborne pathogens Staphylococcus aureus ATCC 6538 and Escherichia coli K12 as the targets.…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxin is a class of secondary metabolites produced by fungi, with high toxicity and carcinogenicity for humans that is most often associated with inadequate storage conditions and often found in bakery products 19 . In this case, an efficient strategy to avoid losses such as prolonging shelf life through the use of packaging and heat treatments is the use of active packaging with oregano EO 20,21 …”
Section: Introductionmentioning
confidence: 99%